Sociálně-psychologické aspekty volby technického a humanitního studijního zaměření při tranzici žáků do maturitních oborů na středních školách. / Social-psychological aspects of choosing technical study fields and humanities completed with school-leaving examination in the pupils' transition to upper-secondary schools. - Petr Hlaďo; Jiří Balcar (Czech Pedagogical Society, 2012)
Education is one of the signiϐicant factors that co-determine the social status of an individual and allow for the lessening of inequalities in a stratification system. The thematic focal point of the paper is thus the choice of upper secondary school, as it significantly pre-determines his/her future eﬀ ectiveness on the labour market and the chance to succeed in the transition to tertiary education. Partial conclusions of a questionnaire survey are presented, which was conducted in 2010 among 9th grade pupils (n = 1526) within the Ostrava district. The study aimed to determine the relationship between social-psychological factors (the educational aspirations of pupils, pupils' attitude towards education, family structure, the education and employment of their parents, their parents' interest in education, the influence of the study environment, etc.) and pupils deciding for an education in technical study fields or the humanities completed with a school-leaving examination at the uppersecondary level.